Effects of Metformin and Metformin Plus Glibenclamide on Glucose-6-Phosphatase Status and Some Biochemical Parameters in Type 2 Diabetic Patients - Hallab, Zainab S; Jawad, Alaa H; Saifullah, Perry H (Al-Nahrain Journal of Science, 2018)
This research was done to assess the effects of anti diabetic drugs (metformin and metformin plus glibenclamide) on Glucose-6-phosphatase activity, serum leptin concentration, Fasting plasma glucose (FPG), Glycated hemoglobin (HbA1c%) and lipid profile in type 2 diabetic patients. The study involved 64 patients suffering from type 2 diabetes mellitus. They were divided into 3 groups. The first group involves 23 newly diagnosed diabetic patients, who did not take any hypoglycemic agents. The second group involves 21 patients on metformin monotherapy, whereas the third group involves 20 patients on metformin plus glibenclamide combination therapy. Another group which involved 20 apparently healthy subjects was used as control group. Age, Body mass index (BMI), FPG, HbA1c %, lipid profile, Glucose-6-phosphatase activity and serum leptin concentration have been determined. The results showed that the activity of Glucose-6-phosphatase was lower in metformin and metformin plus glibenclamide groups when compared with newly diagnosed group and closer to that of control group, leptin concentration was lower in metformin group than that in metformin plus glibenclamide group and these two groups were lower than newly diagnosed group, the levels of FPG, HbA1C% were reduced in metformin and metformin plus glibenclamide groups when compared with newly diagnosed group and metformin alone produce a non-significant favorable effect on all lipids profile parameters, while metformin plus glibenclamide showed a significant reduction in Total Cholesterol (TC) and Low Density Lipoprotein LDL-C. In conclusion, using metformin as a mono therapy or combination with glibenclamide can reduce Glucose-6-phosphatase activity, FPG and HbA1c% levels in type 2 diabetic patients and metformin monotherapy reduced leptin levels more than metformin combination with glibenclamide in type 2 diabetic patients patients so Glucose-6-phosphatase activity and serum leptin concentration can be used as an indicator for the choice of treatment in those diabetic patients.